The Causative in Indonesian - Benedictus Bherman Dwijatmoko (Universitas Sanata Dharma, 2021)
In the Principle and Parameter approach, the Indonesian suffix –kan can be treated as an inflection that functions to create a causative relation between the arguments which the verb takes. Along with the treatment, the voice affixes (Vc) meng-, di-, and ter- also heads a phrase, a Voice Phrase (VcP), and a verbal sentence in Indonesian, which really has the status of a Complementizer Phrase (CP), has a VcP as its main element. Vc may take a VP or any other phrase category including a Causative Phrase (CsP) headed by the suffix –kan as its complement. A CsP can also become the complement or adjunct or a VP or another category phrase which becomes the complement of a VcP. The analysis of the suffix –kan as an inflection can explain the similarity of the pairs of sentences which are syntactically similar and have the same meaning, solve the problem of meaning which usually accompanies the discussion of the suffix, and explain the production of Indonesian sentences which contain the suffix –kan. Furthermore, the study may also provide insights for English and Indonesian course designers to develop materials which can present the topic clearly and for Indonesian and English translators to arrive at a good translation equivalent.